T2DM HEART FAILURE AND FIBROSIS MARKERS CORRELATION - Kumar, Vivek (Student's Journal of Health Research Africa, 2023)
Background: Despite many commonly used antihyperglycemic medications lowering hyperglycemia in type 2 diabetics, heart failure remains a major issue. Thus, variables other than glycemia may increase the risk of heart failure in diabetics. Aim: The primary aim of the current investigation was to assess the correlation between circulating biomarkers indicative of fibrosis and the occurrence of HFpEF in individuals diagnosed with T2DM, undergoing treatment with SGLT2i. Methods: Initially, the study conducted transthoracic echocardiography and laboratory analysis to measure various biomarkers. After a period of three years, data regarding heart failure events, including hospitalizations for heart failure and diagnoses of heart failure in outpatient settings by cardiologists, was collected. Results: Seventy-two patients were included in the study. The mean age was 57 (49.7; 63.2) years; 44% were female. Most patients had T2DM for more than 4 years. All patients were overweight or had obesity, and 93% of patients had arterial hypertension (AH). After 3 years of follow-up, HFpEF was established in 21% of patients. Patients were divided into two groups according to the presence of HFpEF, and baseline characteristics were compared. Patients with HF were older and had longer diabetes and AH duration and higher Nt-proBNP, Gal-3, PIIINP, and PICP levels at baseline than patients without HF (all p < 0:05). Conclusion: with type 2 diabetes mellitus (T2DM) who were given sodium-glucose cotransporter 2 inhibitors (SLGT2i) and developed heart failure with preserved ejection fraction (HFpEF) after a three-year monitoring period had elevated serum concentrations of PICP, PIIINP, Gal-3, and NT-proBNP at the start of the study. Additionally, Gal-3 levels independently predicted HFpEF. Recommendation: SGLT2i are recommended in patients with T2DM at high risk of CV events or with CV disease to reduce hospitalizations for HF, major CV events, and CV death.